Pertanggungjawaban Pidana Anak Sebagai Pelaku Kejahatan Kesusilaan Terhadap Anak - Rahmatyar, Ana; Setiyono, Joko (UNIB Press, 2020)
AbstractThis study aims to look at the accountability of the convict, children who commit decency crimes, especially rape, and to find useful concepts to overcome these crimes. The legal issues discussed in this study include the accountability of children who commit decency crimes in Indonesia and how the idea is useful in overcoming these problems. The research methodology used is